Incidence of Advertising on Public Transport Buses in the Rumiñahui Canton and its Influence on Consumer Behavior - Pineda-López, Rosario del Carmen (2019)
The objective of the present investigation is to determine if the advertising displayed on means of transport in the Rumiñahui Canton has a favorable impact on consumer behavior from the point of view of marketing. The focus of the study is mixed, the type of research is correlational, the design is non-experimental, cross-sectional and allows measuring the correspondence between the variables: mobile outdoor advertising in public transport and consumer behavior variables. A field investigation was conducted through a structured interview, which was validated by 8 experts. Directors of public transport bus cooperatives were consulted and an interview was conducted with a sample of 383 public transport users, by random sampling of the total population of Rumiñahui. For the purpose of analyzing the data collected, a univariate analysis was performed first for each question and then bivariate with the chi-square test to analyze the influence between the dimensions of the variables. The result obtained was the rejection of the null hypothesis originally proposed, concluding that publicity in public transport buses favorably influences the behavior of public transport users as a strategy to encourage consumption.